Food Consumption Pattern of a Sample of Primary School Teachers in Bangladesh - Ahmed, Luthfor; Sarker, Bela Rani (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.69-76